Upaya Peningkatan Komunikasi Pada Klien Isolasi Sosial - Dwi Atmaja, Sarwedi, Arum Pratiwi, S.Kp., M.Kes (2017)
Metode the method of the study is description case study approada, is to perfom nursing care in client with social isolation ranging from assessment, intervention, implementation, and evaluation of nursing. Result the result of this study after the resacher doing examine during three days, the nursing diagnose which occur is disturb of soscial isolation introvert has the correlation with distrubing afther the rasearcher doing at range of nursing education during three days according of planning Condusion according to the result of this reasearch, the research can be show the conclusion that the moment on giving nursing education onthe patient with disturbing social isolation introverts needed doing phenomenological to continual. Keywords social isolation, diagnosis, mental disorders